Exploring the Feelings of Teacher, Student, and Parent: When Learning Virtually during the Covid-19 Pandemic - Hidayati, Istania Widayati; Mujahidun, Mujahidun; Asghari, Seyed Amir Hossein (Universitas Muhammadiyah Magelang, 2021)
Covid-19 pandemic has forced students to study at home, including those with special needs who require physical and non-physical assistance. Meanwhile, online learning has been a bitter choice in creating a variety of experiences. Hence, this study aims to examine the online learning experience in Islamic Religious Education subjects at SLB Ma'arif Muntilan. Furthermore, a qualitative and phenomenological approach was used while the data was collected through interviews, observation, and documentation of teachers, students, and parents who experience online learning during the COVID-19 pandemic. The findings show that teachers, students, and guardians experience dissatisfaction and difficulties, but adjustments are made through coping strategies in order to understand the situation and build serenity.